Radio Bursts With Extragalactic Spectral Characteristics Show Terrestrial Origins - Burke-Spolaor, S.; Bailes, M.; Ekers, Ronald; Macquart, Jean-Pierre; Crawford III, F. (Institute of Physics Publishing, Inc., 2011)
Three years ago, the report of a solitary radio burst was thought to be the first discovery of a rare, impulsive event of unknown extragalactic origin. The extragalactic interpretation was based on the swept-frequency nature of the event, which followed the dispersive delay expected from an extragalactic pulse. We report here on the detection of 16 pulses, the bulk of which exhibit a frequency sweep with a shape and magnitude resembling the Lorimer Burst. These new events were detected in a sidelobe of the Parkes Telescope and are of clearly terrestrial origin, with properties unlike any known sources of terrestrial broadband radio emission. The new detections cast doubt on the extragalactic interpretation of the original burst, and call for further sophistication in radio-pulse survey techniques to identify the origin of the anomalous terrestrial signals and definitively distinguish future extragalactic pulse detections from local signals. The ambiguous origin of these seemingly dispersed, swept-frequency signals suggests that radio-pulse searches using multiple detectors will be the only experiments able to provide definitive information about the origin of new swept-frequency radio burst detections.